Congenital bone malformation in a rainbow boa Epicrates cenchria crassus - case report - Sesoko, Natalia Ferreira [UNESP] (2011)
Bone malformation in snakes stems from inbreeding or temperature variations during gestation or incubation. Differential diagnosis are osteoarthropathy due to nutritional, metabolic and infectious diseases. For an accurate diagnosis of these changes, a radiographic exam is essential because it provides a general view of the skeleton and detects morphological abnormalities. This study aimed to report the clinical care of a rainbow boa (Epicrates cenchria crassus) with congenital kyphosis and changes in scales, from a snake pit with controlled temperature and humidity since its gestation. Multiple dorsal deviations of the column without the presence of osteoarthrosis were seen upon radiographic examination. Studies aiming to understand the cases of congenital malformation in snakes should be performed to prevent the birth of animals with this type of change.